Initial experiences using plasma rich in growth factors to treat keratoneuralgia - Wang, Margaret; Yennam, Sowmya; Pflugfelder, Stephen (Frontiers in Medicine, 2022)
Keratoneuralgia, a clinical diagnosis of sensitized corneal pain without visible ocular surface damage, generally has minimal response to conventional therapies. Causes include refractive surgery and chronic dry eye. We evaluated the efficacy of Plasma Rich in Growth Factors (PRGF), a novel treatment prepared using a commercially available kit, in patients with keratoneuralgia. A retrospective chart review identified patients who had the clinical diagnosis of keratoneuralgia and were treated with PRGF for at least 3 months from October 2015 to April 2020 at a single academic institution. Both objective eye exam findings and concurrent treatments were obtained at baseline, 3 months, and final visit (if available). A questionnaire was administered to identified patients, including symptoms scores measured with a visual analog scale. The results of this survey and other objective findings were compared before and after PRGF treatment. 16 out of 32 patients (50%) with a mean follow-up period of 33 +/- 26 months answered the questionnaire. Refractive surgeries were the cause of keratoneuralgia in 14 patients (87.5%), with LASIK the most common procedure (11 patients, 69%). There were no adverse events recorded or reported. Symptom scored by VAS in a modified Symptoms Assessment in Dry Eye questionnaire significantly decreased after PRGF use (85 +/-16 to 45 +/- 33, p=0.0002). 10 patients (63%) reported PRGF is superior to other therapy and would recommend to others. There were no significant trends in visual acuity, objective exam findings, or concurrent treatments after PRGF treatment. PRGF is safe and can potentially alleviate symptoms in patients with keratoneuralgia, a rare but devastating complication after refractive surgery. Prospective trial is indicated to explore PRGF as a potentially useful treatment for keratoneuralgia.